WORK STUDY CONFLICT AGAINST BURNOUT: THE MODERATION ROLE OF SOCIAL SUPPORT FROM FRIENDS - Kurniawan, Pebi; Jufri, Ali; Gunawan, Asep; Andre Yani, Selvia; Priyono, Dadang (Dinasti International Journal of Management Science, 2021)
The conflict between work and family roles has been widely studied. However, recently, research has progressed to study roles outside of work and family. For example, several researchers have investigated the conflict between work and educational roles. However, this study focuses on the occurrence of burnout. Thus this study seeks to contribute to the literature on work-education conflict in two main ways. First, we investigate the relationship between work study conflicts and the occurrence of burnout. Furthermore, to prove the role of social support from friends as a moderating variable. Participants in this study were 81 students. The results of this study support our proposed hypothesis.